Comparison of skinfold thicknesses and bioelectrical impedance analysis with dual-energy X-ray absorptiometry for the assessment of body fat in patients on long-term haemodialysis therapy - Kamimura, Maria Ayako [UNIFESP] (2016)
Background. Body composition assessment in patients with chronic renal failure is of paramount importance since studies have demonstrated the association of protein-energy malnutrition with an increased morbidity and mortality in this population. However, practical and sensible indicators of body compartments are still needed for clinical purposes. Thus, we aimed to evaluate the simple methods of skinfold thicknesses, (SKF) and bioelectrical impedance analysis (BIA) using dual-energy X-ray absorptiometry (DEXA) as a reference method, for the assessment of body fat. in patients on long-term haemodialysis therapy.Methods. We studied 30 clinically stable patients (15 men/15 women) undergoing haemodialysis at the Dialysis Unit of the Federal University of São Paulo. Body fat assessment was performed by the SKF, BIA and DEXA methods after a haemodialysis session. Analysis of variance, intra-class correlation coefficient and Bland and Altman plot analysis were used for comparative analysis among the methods.Results. Body fat estimates by SKF (17.7 +/- 7.8 kg) and BIA (18.6 +/- 9.2 kg) were not significantly different from those obtained by DEXA (18.2 +/- 7.9 kg) considering the whole population. However, the BIA technique worked differently from DEXA when analysed by gender, measuring less fat content in men and higher fat content in women (P < 0.01). No differences were observed for SKF. Strong intra-class correlation coefficients (r) were found between DEXA with SKF (r = 0.94) and BIA (r = 0.91). DEXA showed a relatively good agreement with both SKF [0.47 +/- 2.8 (-5.0 to 6.0) kg] and BIA [-0.39 +/- 3.3 (-6.9 to 6.1) kg] in all patients according to the Bland and Altman plot analysis. However, considering gender, BIA showed greater mean prediction error of 1.93 +/- 2.5 (-3.0 to 6.8) kg for men and -2.71 +/- 2.3 (-7.2 to 1.8) kg for women.Conclusions. the simple and long established method of SKF was preferable over BIA, which showed gender-specific variability in the assessment of body fat in patients undergoing haemodialysis. However, more comparative and longitudinal studies are needed to evaluate the applicability of these practical methods for monitoring body composition in the routine care of patients with chronic renal failure.